The Path of Kebaya Women :The Role of The Syarikat Islam Women’s Movement in Indonesia’s Development and Politics, 1966-1975 - Kusairi, Latif; Refanda Pratiwi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the role of Wanita Syarikat Islam, known during the period as Gerwapsi (Gerakan Wanita Syarikat Islam), in Indonesia’s political landscape between 1966 and 1975. Despite the extensive attention given to Syarikat Islam as a broader movement, the specific contributions of Gerwapsi have been largely neglected in academic historiography. This research aims to address that gap by highlighting the organization’s political activism during the crucial transition from the Sukarno to the Suharto regime. Employing a qualitative-descriptive method within a historical framework, the study utilizes primary sources including archival records, photographs, period newspapers, interviews with historical actors, and autobiographies. Data validity is reinforced through triangulation and cross-referencing of multiple source types. Findings indicate that Gerwapsi significantly influenced political discourse and decision-making during the New Order’s early years. The organization participated in efforts to attribute responsibility for the G30S/PKI incident to Sukarno, contributed to the formulation of the Islamic Marriage Law, and advocated for the repeal of Presidential Regulation No. 2 of 1959. Gerwapsi also led initiatives against gambling, prostitution, and human trafficking. These roles demonstrate that Gerwapsi was more than an auxiliary women's group; it was a central political actor. This study offers a vital addition to research on women’s political movements in modern Indonesian history.